1987
DOI: 10.1007/bf01310719
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunological characterization of structural proteins from retrovirus-D/New England and comparison to Mason-Pfizer monkey virus and permanent human fibroblast virus

Abstract: Biochemical and immunological properties of retrovirus-D/New England (here referred as R-D/NE) recently isolated at the New England Regional Primate Research Center, Southborough, Ma, from a rhesus monkey with acquired immune deficiency syndrome were investigated and compared to the prototype type D retroviruses Mason-Pfizer monkey virus (MPMV) and permanent human fibroblast virus (PMFV) isolated from a breast carcinoma of a rhesus monkey and a continuous human cell line, respectively. The polypeptide composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Deletion assays indicated that the phosphorylated residue Y205 in pp18 is dispensable for capsid assembly, but is necessary for the viral release [112]. Immunoprecipitation experiments identified the presence of phosphoserines in pp18, [113,114] displaying a redundant character. Similarly, for spumaviruses such as FV, mapping of the p4 domain revealed that seven residues can be phosphorylated (Table 2), but a single substitution of those residues displayed no influence on viral replication [115].…”
Section: Gag Phosphorylation In Other Retrovirusesmentioning
confidence: 99%
“…Deletion assays indicated that the phosphorylated residue Y205 in pp18 is dispensable for capsid assembly, but is necessary for the viral release [112]. Immunoprecipitation experiments identified the presence of phosphoserines in pp18, [113,114] displaying a redundant character. Similarly, for spumaviruses such as FV, mapping of the p4 domain revealed that seven residues can be phosphorylated (Table 2), but a single substitution of those residues displayed no influence on viral replication [115].…”
Section: Gag Phosphorylation In Other Retrovirusesmentioning
confidence: 99%